2007
DOI: 10.1152/ajpcell.00504.2006
|View full text |Cite
|
Sign up to set email alerts
|

Myogenic differentiation during regrowth of atrophied skeletal muscle is associated with inactivation of GSK-3β

Abstract: van der Velden JL, Langen RC, Kelders MC, Willems J, Wouters EF, Janssen-Heininger YM, Schols AM. Myogenic differentiation during regrowth of atrophied skeletal muscle is associated with inactivation of GSK-3␤.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 64 publications
2
42
1
Order By: Relevance
“…Reloading-induced upregulation of muscle OXPHEN may well involve myogenesis-induced development of muscle OXPHEN. Indeed, muscle reloading has been shown to be associated with muscle regeneration, which involves myogenesis (19,37,43). Moreover, we and others have convincingly shown, not only that myogenesis and muscle regeneration are associated with a potent induction of mitochondrial biogenesis and activation of PGC-1-coactivated signaling events (32,47), but also that myogenesis and myogenesis-induced activation of oxidative metabolism are highly interdependent processes (18,34).…”
Section: E619 Alternative Nf-b Signaling During Recovery Of Muscle Oxmentioning
confidence: 59%
“…Reloading-induced upregulation of muscle OXPHEN may well involve myogenesis-induced development of muscle OXPHEN. Indeed, muscle reloading has been shown to be associated with muscle regeneration, which involves myogenesis (19,37,43). Moreover, we and others have convincingly shown, not only that myogenesis and muscle regeneration are associated with a potent induction of mitochondrial biogenesis and activation of PGC-1-coactivated signaling events (32,47), but also that myogenesis and myogenesis-induced activation of oxidative metabolism are highly interdependent processes (18,34).…”
Section: E619 Alternative Nf-b Signaling During Recovery Of Muscle Oxmentioning
confidence: 59%
“…The last two decades, several studies addressed complementation of this approach with muscle growth-stimulating pharmaceuticals, including anabolic steroids (20,22). Many of the effects of anabolic steroids are a consequence of increased androgen receptor-mediated expression of IGF-I in skeletal muscle, which, in an auto/paracrine fashion, induces local IGF signaling and subsequent muscle growth (18,23,41,44,50). Therefore, we used IGF-I to model these steroid effects on myogenesis, which is an important component of muscle regrowth.…”
Section: Discussionmentioning
confidence: 99%
“…This relies on reduced activity of mammalian target of rapamycin (mTOR) complex-1 (mTORC1) and decreased phosphorylation of its downstream targets p70-S6K1 and 4E-BP1, which stimulate translation capacity and suppress translation initiation, respectively (14,17,27,34,37,54,58). Conversely, anabolic steroids, like nandrolone decanoate (ND), prevent muscle atrophy and stimulate muscle growth and hypertrophy, partly by increasing muscle insulin-like growth factor (IGF)-I production and signaling in a para/autocrine fashion (18,23,41,44,50). In contrast to GC, IGF-I signaling reduces proteolysis and increases protein synthesis, including mTORC1 signaling (17,45).…”
mentioning
confidence: 99%
“…At the same time, some authors did not find an increase in phosphorylated p70s6k (Thr389) in soleus after 10 days of mechanical unloading [22]. Van der Velden co-authors did not observe any changes in the phosphorylation status of both AKT (Ser473) and GSK-3β (Ser9) in soleus of mice following 14-day HS [23]. However, White et al reported a decrease in AKT and GSK-3β phosphorylation in rat soleus muscle after 2-week unloading [24].…”
Section: Introductionmentioning
confidence: 94%